Impact of Ship Traffic on the Characteristics of Shelf Sediments: An Anthropocene Prospective - Xue, Chengfeng; Yang, Yang; Zhao, Peipei; Wei, Dongyun; Gao, Jianhua; Sun, Peng; Huang, Zhiyang; Jia, Jianjun (Frontiers in Marine Science, 2021)
Humans have been sailing across seas and oceans for thousands of years. However, the story of large ships capable of affecting coastal ecology and shelf sedimentary processes is only about 100 years old. Modern large seagoing vessels with a draft of 10–20 m can cause resuspension of seabed sediment, erosion of the channel slope and shoal, enhancement of seafloor sediment activity and thickening of the active layer, thereby having a significant impact on seabed topography and sedimentation processes. However, little is known about the effects of this anthropogenic agent on shelf sedimentation due to limited observational data. Here, two sediment cores were collected from a shipping lane used by vessels of 5,000- to 50,000-ton off the coast of China to analyze their sedimentary properties, with focus on both the grain size and elements. It was found that ship disturbance selectively modified the sedimentary record, with the fine-grained sediment becoming increasingly unstable. In addition, there was a reduction in grain size of sediment finer than 6.25 Φ, which decreased by 11% after the disturbance by ship. Biogenic elements that were closely related to the ecological environment were significantly altered, with Br/Cl, Si/Ti, and Ca/Ti ratios all becoming significantly smaller. This indicated that frequent disturbance caused by ships had reduced the productivity in the waters near the shipping lane. In terms of sensitivity to the effects of ship navigation, the sedimentation response was relatively rapid and began to emerge from the commencement of ship navigation, whereas the ecological response became evident later than the sedimentation response and only appeared after a significant growth in the maritime transportation of China. Following the comparison of the two sediment cores, we propose that the constant rate of supply (CRS- with ship disturbance)–constant initial concentration (CIC- without ship disturbance) dual dating model be used to establish a dating framework in waters frequently disturbed by ship. This type of anthropogenic sedimentary dynamic process and its sedimentary–ecological effects deserve attention on this era where there is a surge in shipping globally. Shipping lanes present an excellent area for quantitative studies on the impacts of human activity and defining the Anthropocene in the context of shipping.